1999
DOI: 10.1046/j.1365-294x.1999.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Do assemblages of Coregonus (Teleostei: Salmoniformes) in the Central Alpine region of Europe represent species flocks?

Abstract: To examine models of evolution for Coregonus from the Central Alpine region of Europe, 20 populations from nine lakes were assessed for variation at six microsatellite DNA loci. Patterns of variation were tested against three evolutionary models: phenotypic plasticity, multiple invasions of lakes by divergent forms, and within‐lake radiation of species flocks. All sympatric and all but one allopatric pairs of populations were significantly divergent in allele frequencies. Pairwise F‐statistics indicated reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
129
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 92 publications
16
129
2
1
Order By: Relevance
“…The molecular analysis presented in this paper is the first attempt to compare genetic diversity (based on microsatellite DNA analysis) of two Polish natural populations of whitefish and two aquaculture broodstocks of this fish species. In this study, the mean number of alleles (5.1-10.2), allele richness (1.13-14.00), and the observed heterozygosity (0.48-0.57) parameters in the analyzed groups of whitefish were comparable to reports from studies on other whitefish populations (Douglas et al 1999;Lu and Bernatchez 1999;Stott et al 2004). For example, the average heterozygosity in the six populations of whitefish studied by Lu and Bernatchez (1999) ranged from 0.42 to 0.63.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The molecular analysis presented in this paper is the first attempt to compare genetic diversity (based on microsatellite DNA analysis) of two Polish natural populations of whitefish and two aquaculture broodstocks of this fish species. In this study, the mean number of alleles (5.1-10.2), allele richness (1.13-14.00), and the observed heterozygosity (0.48-0.57) parameters in the analyzed groups of whitefish were comparable to reports from studies on other whitefish populations (Douglas et al 1999;Lu and Bernatchez 1999;Stott et al 2004). For example, the average heterozygosity in the six populations of whitefish studied by Lu and Bernatchez (1999) ranged from 0.42 to 0.63.…”
Section: Discussionsupporting
confidence: 88%
“…Data on genetic variability within and among populations are also useful for fisheries researchers and managers because such results can provide information on stock or population subdivision and relatedness in fish (Patton et al 1997) or on hybridization events among closely related species. Genetic studies on European whitefish have been conducted by several authors, who applied various types of genetic analyses among protected natu- (Douglas et al 1999;Hansen et al1999;Ostbye 2005). Molecular genetics has generated many important and powerful methods useful for fish breeding in aquaculture, especially when a valuable fish broodstock must be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genotypic examinations of the central alpine Coregonus species have revealed that the indigenous Coregonus populations of Switzerland are distinct, with their closest relatives within the same lakes (Douglas et al 1999). The significant differences in allele frequency found among the different ecotypes in Lake Thun indicates a reduced gene flow among phenotypically divergent sympatric populations (Douglas et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Within the Alpine whitefish radiation intralacustrine diversity varies from one to six species. Coexisting species are genetically differentiated [18], and phenotypically differentiated in traits linked to feeding ecology: gill-raker number and density, growth rate, shape and colour and also in traits linked to reproductive ecology: time of spawning, location/depth of spawning, spawning substrate and egg size, with the replicated occurrences of corresponding ecotypes in different lakes [19,20]. Previous phylogeographic studies of the Coregonus lavaretus species complex have shown two very divergent mitochondrial lineages present among the Alpine whitefish [21,22].…”
Section: Introductionmentioning
confidence: 99%